Seed germination, respiratory processes and phosphatidic acid accumulation in Arabidopsis diacylglycerol kinase knockouts - The effect of brassinosteroid, brassinazole and salinity - Derevyanchuk, Michael; Kretynin, Sergii; Kolesnikov, Yaroslav; Litvinovskaya, Raisa; Martinec, Jan; Khripach, Vladimir; Kravets, Volodymyr (Steroids, 2019)
Using Arabidopsis thaliana wild type (WT) plants and diacylglycerol kinase knockouts (single mutants - dgk3, dgk1, dgk6; double mutants - dgk3dgk7, dgk5dgk6, dgk1dgk2) we observed that the inhibitor of brassinosteroid (BR) biosynthesis, brassinazole (BRZ), drastically decreased germination of dgk mutants under salt stress, while BRZ co-administration with 24-epibrassinolide (EBL) partially improved germination rates. We also observed a statistically significant decrease in alternative and cytochrome respiratory pathways in response to BRZ treatment under salinity conditions. We showed that production of the lipid second messenger phosphatidic acid (PA) is impaired in dgk mutants in response to EBL treatment and inhibitor of diacylglycerol kinase (DGK) - R59022. This study demonstrates that dgk mutants possess lower germination rates, lower total respiration rates, an alternative respiratory pathway and PA content under optimal and high salinity conditions in response to EBL treatment comparing to WT plants.
Keywords: Brassinosteroids; Triazoles; diacylglycerolkinasa; salinita; semena rostlinná; Diacylglycerol Kinase; Arabidopsis thaliana; Phosphatidic acid; Phosphatidic Acids; Salinity; Seeds; triazoly; Diacylglycerol kinase; kyseliny fosfatidové; brassinosteroidy; Arabidopsis; Alternative oxidase